Hubungan Asupan Zat Besi dan Status Gizi dengan Derajat Dismenore pada Mahasiswi Gizi di UHAMKA - Nastiti Indriati, Sally; Rahayu, Leni Sri; Aini, Rahmatika Nur (Media Gizi Ilmiah Indonesia, 2024)
Dysmenorrhea is a pain that is felt by women of reproductive age during menstruation. Moderate-severe dysmenorrhea is known to have a negative effect on academics and daily activities compared to mild dysmenorrhea. One of the nutrients that can overcome dysmenorrhea is iron. Meanwhile, abnormal nutritional status will worsen the degree of dysmenorrhea. The aim of the study is to determine the relationship between intake of iron, nutritional status, and the degree of dysmenorrhea in UHAMKA nutrition students. This research uses quantitative methodology with a cross-sectional study design and sampling using a purposive random sampling technique. The data were obtained by interviewing the Semi-Food Frequency Questionnaire (SQ-FFQ), and the status of the data was obtained by measuring weight and height. Data analysis using the Chi-Square test. The results showed that as many as 78.3% of the subjects experienced moderate-severe dysmenorrhea. There was a no relationship between intake of iron (P = 0.110) and nutritional status (P = 0.512) with the degree of dysmenorrhea. There is no significant relationship between intake of iron and nutritional status with degree of dysmenorrhea in UHAMKA nutrition students